Tumor-like presentation of herpetic cervicitis: A case report - Pablo Boldrini L.; Gabriel Vallejos P.; Polentze Ballesteros P.; Gonzalo Valenzuela L.; Enrique Roncone D. (Elsevier, 2023)
The case of a 20-year-old immunocompetent woman with necrotizing cervicitis of the cervix caused by a primary infection with herpes simplex virus type 2 is presented, along with its respective evolution in images. Cervical cancer was included in the differential diagnoses, but biopsies ruled out malignancy and laboratory tests demonstrated the viral etiology of the cervical inflammation. After initiating specific treatment, the cervical lesions completely healed within 3 weeks. This case highlights the need to consider herpes simplex infection in the differential diagnosis of cervical inflammation and tumor formation. Additionally, it provides images that can aid in diagnosis and allow for the observation of its clinical evolution.